2020
DOI: 10.1101/2020.11.04.368746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

E-cadherin interacts with EGFR resulting in hyper-activation of ERK in multiple models of breast cancer

Abstract: The loss of the intercellular adhesion molecule E-cadherin is a hallmark of the epithelial-mesenchymal transition (EMT), which promotes a transition of cancer cells to a migratory and invasive phenotype. E-cadherin is associated with a decrease in cell proliferation in normal cells. Here, using physiologically relevant 3D in vitro models, we find that E-cadherin induces hyper-proliferation in breast cancer cells through activation of the Raf/MEK/ERK signaling pathway. These results were validated and consisten… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 62 publications
(137 reference statements)
4
27
0
Order By: Relevance
“…1c). This enhanced E-cad dependent proliferation is maintained at all collagen concentrations, supporting the previously reported hyper-proliferation observed in 3D cultures [27]. Regarding the effects of the ECM on cancer cell proliferation, we observe that softer matrices (1 mg/mL) promote higher proliferation rates than stiffer matrices regardless of E-cad expression (Fig.…”
Section: Cancer Cell Proliferation Is Promoted By E-cad and Limited B...supporting
confidence: 90%
See 4 more Smart Citations
“…1c). This enhanced E-cad dependent proliferation is maintained at all collagen concentrations, supporting the previously reported hyper-proliferation observed in 3D cultures [27]. Regarding the effects of the ECM on cancer cell proliferation, we observe that softer matrices (1 mg/mL) promote higher proliferation rates than stiffer matrices regardless of E-cad expression (Fig.…”
Section: Cancer Cell Proliferation Is Promoted By E-cad and Limited B...supporting
confidence: 90%
“…E-cad is a transmembrane protein that is ubiquitously expressed in non-invasive epithelial and tumor cells prior to their epithelial-mesenchymal transition (EMT) [19]. For this reason, it was believed to be a tumor-suppressor gene, and its loss a prerequisite for tumor metastasis; however, this hypothesis has been recently questioned [25, 26, 27]. We showed that E-cad expression results in hyper-proliferation of breast cancer cells by promoting activation of the ERK cascade utilizing a similar 3D organoid model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations